A FABP4-PPARγ signaling axis regulates human monocyte responses to electrophilic fatty acid nitroalkenes - Lamas Bervejillo, M. (2020)
Nitro-fatty acids (NO2-FA) are electrophilic lipid mediators derived from unsaturated fatty acid nitration. These species are produced endogenously by metabolic and inflammatory reactions and mediate anti-oxidative and anti-inflammatory responses. NO2-FA have been postulated as partial agonists of the Peroxisome ProliferatorActivated Receptor gamma (PPARγ), which is predominantly expressed in adipocytes and myeloid cells. Herein, we explored molecular and cellular events associated with PPARγ activation by NO2-FA in monocytes and macrophages. NO2-FA induced the expression of two PPARγ reporter genes, Fatty Acid Binding Protein 4 (FABP4) and the scavenger receptor CD36, at early stages of monocyte differentiation into macrophages. These responses were inhibited by the specific PPARγ inhibitor GW9662. Attenuated NO2-FA effects on PPARγ signaling were observed once cells were differentiated into macrophages, with a significant but lower FABP4 upregulation, and no induction of CD36. Using in vitro and in silico approaches, we demonstrated that NO2-FA bind to FABP4. Furthermore, the inhibition of monocyte FA binding by FABP4 diminished NO2-FA-induced upregulation of reporter genes that are transcriptionally regulated by PPARγ, Keap1/Nrf2 and HSF1, indicating that FABP4 inhibition mitigates NO2-FA signaling actions. Overall, our results affirm that NO2-FA activate PPARγ in monocytes and upregulate FABP4 expression, thus promoting a positive amplification loop for the downstream signaling actions of this mediator.